Konzept und studentische Evaluation der Integrierten Seminare im Studienabschnitt "Medizin I" der Medizinischen Fakultät der Universität Hamburg [Concept and evaluation of the integrated seminars during pre-clinical studies ("Medicine I") at Hamburg Medical School] - Weidtmann, Katja; Harendza, Sigrid; Dietsche, Stefan; Guse, Andreas H.; Middendorff, Ralf; Schultz, Jobst-Hendrik; Mihalache, Ioan; Frost, Maike; Kuhnigk, Olaf (GMS Zeitschrift für Medizinische Ausbildung, 2007)
[english] Aims: The new law for medical education (ÄAppO 2002) requires the establishment of at least 98 hours of integrated seminars with inclusion of appropriate clinical subjects. The newly established curriculum committee for the reform of pre-clinical studies (Medicine I) developed a concept for these integrated seminars at Hamburg Medical School. The seminars are taught during the first four semesters every fortnight. Subjects of the seminars are related to other courses taking place at the same time. Important didactic elements of the seminars are multidisciplinarity and case based learning. Other elements are small group work, self- study and short student presentations. Representatives from the different scientific and clinical subjects developed horizontal and vertical connections within Medicine I by planning these seminars.Methods: Integrated seminars were evaluated by the first cohort of students between 2003 and 2005 for quality control. With special instruments seminars were evaluated formatively for each seminar and summatively at the end of every semester. Besides descriptive explanations data were analyzed for systematic connections and differences.Results: Evaluation of the integrated seminars at Hamburg Medical School by students from the first cohort demonstrated high acceptance of the concept. Certain aspects of the course like practical relevance of basic sciences, integration of basic sciences and individual learning progress reached high marks of satisfaction.Conclusion: The integrated seminars at Hamburg Medical School represent a coherent concept for horizontal and vertical connection of scientific and clinical aspects which is well accepted by the students. Evaluation results also indicate possibilities of improvement which will be addressed by modification of individual cases and in the faculty development program. [german] Zielsetzung: Die neue ÄAppO (2002) fordert für den ersten Studienabschnitt (Medizin I) die Einrichtung von mindestens 98 Stunden Integrierter Seminare unter Einbezug geeigneter klinischer Fächer. Das an der Medizinischen Fakultät der Universität Hamburg zur Reform des Studienabschnitts Medizin I eingesetzte Curriculum-Komitee erarbeitete ein Konzept für Integrierte Seminare, die in den ersten vier Semestern in 14-tägigem Rhythmus durchgeführt werden. Die Themen orientieren sich inhaltlich an parallel stattfindenden Unterrichtsveranstaltungen. Wichtige didaktische Elemente der Integrierten Seminare sind Interdisziplinarität und das fallbasierte Lernen. Darüber hinaus prägen die Veranstaltung Kleingruppenarbeit, Selbststudium und Kurzreferate. Vertreter naturwissenschaftlicher und medizinischer Grundlagenfächer sowie klinischer Fächer erarbeiteten durch das Seminar horizontale und vertikale inhaltliche Verknüpfungen im Abschnitt Medizin I.Methodik: Zur Qualitätskontrolle wurden die Integrierten Seminare der ersten Studierendenkohorte von Wintersemester 2003/04 bis Sommersemester 2005 wissenschaftlich begleitet. Anhand spezieller Instrumente wurde die Veranstaltung mit Terminevaluationen formativ und mit Abschlussevaluationen summativ evaluiert. Neben einer deskriptiven Darstellung wurden die Daten auf systematische Zusammenhänge und Unterschiede analysiert.Ergebnisse: Die Evaluation der Integrierten Seminare durch die erste Studierendenkohorte belegt eine große Akzeptanz des Konzepts und eine hohe Zufriedenheit mit zentralen Einzelaspekten der Veranstaltung, z. B. Verdeutlichung der Praxisrelevanz der Grundlagenfächer, Aufzeigen der Vernetzung der Grundlagenfächer und subjektiver Lernerfolg.Schlussfolgerung: Die Integrierten Seminare an der Hamburger Medizinischen Fakultät liefern ein schlüssiges und von den Studierenden akzeptiertes Konzept für horizontale und vertikale inhaltliche Verknüpfungen von Grundlagenfächern mit klinischen Fächern. Außerdem zeigen die Evaluationsergebnisse Verbesserungsmöglichkeiten auf, die u. a. durch Modifikationen einzelner Fallgeschichten und im Faculty-Development-Programm der Fakultät umgesetzt werden können.